Effect of Oral to Subcutaneous Switch of Methotrexate on Disease Activity in Rheumatoid Arthritis Patients - Lale Akbulut Aktekin; Filiz Eser; Hatice Bodur; Ahmet Tutoğlu (Archives of Rheumatology, 2009)
Objective: The aim of this study was to evaluate the effect of switching to subcutaneous (sc) methotrexate (MTX) from oral MTX treatment on disease activity in rheumatoid arthritis (RA) patients. Material and Methods: The efficacy of MTX usage and its administration route on disease activity in RA patients were evaluated retrospectively in patients who received oral MTX first and were afterwards switched to sc MTX. Erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) values, DAS 28 disease activity score and side effects were recorded before initiation of oral MTX treatment (baseline), at the time of switch to sc MTX, and at 6th and 12th months of sc MTX usage. The reasons for switching the treatment route were recorded. Results: Sixteen (80%) female and 4 (20%) male subjects, with an average age of 50.25±12.35 years (29-70), were included in the study. Reductions in DAS 28 values were significant between baseline and at the time of switch to sc MTX and between initiation of sc MTX and at 6th months of sc MTX treatment. There were no significant side effects leading to discontinuation of the sc MTX treatment. Conclusion: MTX therapy may be switched from oral to sc form before the other disease-modifying drugs when the drug is inefficient in controlling disease activity or causes gastrointestinal side effects in RA patients. (Turk J Rheumatol 2009; 24: 140-3)